2021
DOI: 10.21138/bage.3006
|View full text |Cite
|
Sign up to set email alerts
|

La sostenibilidad económica de las ayudas al turismo rural del Método Leader en áreas de montaña: dos casos de estudio españoles (Valle del Jerte y Sierra de Gata, Extremadura)

Abstract: Extremadura recibe desde hace 25 años fondos de la Unión Europea, aplicados bajo el Método Leader, encaminados a mantener la población y a complementar las rentas agrarias de las zonas rurales. Una de las actividades que más se ha promocionado ha sido el turismo mediante la creación de una oferta (alojamientos y de servicios de restauración), que sirva de soporte para satisfacer las necesidades de una creciente demanda. Sin embargo, el estudio del mantenimiento de dichas infraestructuras ha sido escasamente an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Cluster analysis has made it possible to determine the importance of the investment volume variable in the survival of tourism infrastructures, but it is complemented by others. In other studies, different authors have shown that investment is a factor that has conditioned the success of the projects financed by Leader and that it is usually located in those areas where there is a larger population and a previous economic fabric [49,63,64] that has the capacity to co-finance the investments received by Leader. These municipalities would correspond to the typology of results shown in Group 2 (high population volume, demographic dynamism, investments and high private participation, but which, if estimated in relation to their population are not so high) and which have mainly financed hotel infrastructures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cluster analysis has made it possible to determine the importance of the investment volume variable in the survival of tourism infrastructures, but it is complemented by others. In other studies, different authors have shown that investment is a factor that has conditioned the success of the projects financed by Leader and that it is usually located in those areas where there is a larger population and a previous economic fabric [49,63,64] that has the capacity to co-finance the investments received by Leader. These municipalities would correspond to the typology of results shown in Group 2 (high population volume, demographic dynamism, investments and high private participation, but which, if estimated in relation to their population are not so high) and which have mainly financed hotel infrastructures.…”
Section: Discussionmentioning
confidence: 99%
“…- As for the context variables, a series of demographic, economic and accessibility variables were used to carry out the research analysis (Table 2): These variables have been selected as the most representative after the analysis and review of different scientific studies. Studies such as those carried out by Santos et al [44] in Portugal or Navarro et al [43] in Andalusia (Spain) have determined that the success of Leader Method projects is determined by variables such as the location, the investment made or the economic and demographic characteristics of the territories themselves or previous studies carried out by the authors in the study region [49], where it is stipulated, with a correlation analysis, that variables such as proximity to the main communication routes and cities, the existence of a previous business fabric and location in irrigated agricultural areas are influencing the concentration of investments. Other previous studies in Extremadura have also analyzed investments in rural tourism [20,22].…”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are marked imbalances in rural tourism promotion [30], with the interests of each party prevailing over the construction of a joint destination, with the DSMBR being an opportunity, as highlighted by the NtPs directors (Int03, In08, Int09). The initiatives have been an uneven success, depending on investment, location, presence of protected resources and accessibility for tourist survival [154].…”
Section: The Territorial Dimension Of Local Developmentmentioning
confidence: 99%
“…This is confirmed in different investigations that focus their analysis on the effects of LEADER programmes in such areas as well as the ongoing existence of subsidized business based on tourism projects. (González y Macías, 2014;Arcila y López, 2015;Paül et al, 2016;Navarro et al, 2018;Moriche et al, 2021). The study of Sierra de Gata and the Jerte Valley shows that approximately the 50% of business projects related to tourist accommodation closed after few years of being open (Moriche et al, 2021).…”
Section: Final Remarksmentioning
confidence: 99%